Notes: Categorical Outputs in Data Envelopment Analysis - Rousseau, John J.; Semple, John H. (Management Science, 1993)
A new linear programming formulation for handling categorical outputs in DEA is presented which eliminates the difficulties of interpretation and computation that accompanied earlier mixed integer models.